2016
DOI: 10.19148/ijhbs.02348
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach of Erikson’s Psychosocial Theory and Adlerian Counseling

Abstract: This study aims to integrate Erikson's psychosocial theory and Adler's individual psychology. Adler and Erikson have complimentary descriptions of personality and they both view mankind as a social being in nature, having a desire to belong and motivated for significance in their social environment in order to handle with inferiority. The integration also suggests that four main areas should be taken in consideration during the counseling process: work, friendship, sexual love, and optimism. This integration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…This is not only to prevent and/or successfully intervene in internet addiction at any given time but also to prepare individuals for difficult situations, such as the COVID-19 pandemic, to help them to overcome such difficult situations by using more productive coping strategies and without extreme fear and/or anxiety. It is suggested that inferiority feelings are rooted in childhood, resulting from being subjected to dysfunctional parenting (Adler, 1982(Adler, , 1996 and/or failing at specific learning tasks at school (Çelik and Ergün, 2016). This study thus highlights the importance of functional parenting and experiencing a sense of accomplishment in the early years of life so that inferiority feelings do not increase to a point where they interfere with an individual's ability to successfully regulate their emotions and develop effective coping mechanisms.…”
Section: Discussionmentioning
confidence: 78%
“…This is not only to prevent and/or successfully intervene in internet addiction at any given time but also to prepare individuals for difficult situations, such as the COVID-19 pandemic, to help them to overcome such difficult situations by using more productive coping strategies and without extreme fear and/or anxiety. It is suggested that inferiority feelings are rooted in childhood, resulting from being subjected to dysfunctional parenting (Adler, 1982(Adler, , 1996 and/or failing at specific learning tasks at school (Çelik and Ergün, 2016). This study thus highlights the importance of functional parenting and experiencing a sense of accomplishment in the early years of life so that inferiority feelings do not increase to a point where they interfere with an individual's ability to successfully regulate their emotions and develop effective coping mechanisms.…”
Section: Discussionmentioning
confidence: 78%
“…Inferiority is a psychological structure emphasized in Erikson's psychosocial theory and Adler's personal psychology (Çelik & Ergün, 2016). It is a subjective feeling produced by comparing oneself with others (Strano & Dixon, 1990).…”
Section: The Mediating Role Of Feeling Of Inferiority and Family Cohe...mentioning
confidence: 99%
“…Children's development theories of Sigmund Freud, John Watson and Jean Piaget focused on the significant role of the child's surrounding built environment in his/her development, as children in kindergarten age (4–7 years) cognitively develop through exploration and spatial perception (Bell, 2007; Çelik and Ergün, 2016; Nelson et al , 2007). In light of these theories, it is inevitable that the school environment must work to develop the child's sensation, perception and cognitive development using creative mental and sensory activities, in order to have a positive impact on his/her psychology (Dinchiiska, 2004).…”
Section: Introductionmentioning
confidence: 99%